A Unified Type System for Object-Oriented Programming - Palsberg, Jens; Schwartzbach, Michael I. (DAIMI Report Series, 1990)
We present a new type system for object-oriented languages with assignments. Types are sets of classes, subtyping is set inclusion, and genericity is class substitution. The type system enables separate compilation, and unifies, generalizes, and simplifies the type systems underlying SIMULA/BETA, C++, EIFFEL, and Typed Smalltalk, and the type system with type substitutions proposed by Palsberg and Schwartzbach, Classes and types are both modeled as node-labeled, ordered regular trees; this allows an efficient type-checking algorithm.